Processes Contributing to the Maintenance of Flying Phobia: A Narrative Review - Clark, Gavin I.; Rock, Adam J. (Frontiers in Psychology, 2016)
Flying phobia is a highly prevalent anxiety disorder, which causes sufferers significant distress and life interference. The processes which maintain flying phobia remain poorly understood. A systematic search of the literature was performed to identify what research has been conducted into the processes which may be involved in the fear of flying and whether processes which are believed to maintain other anxiety disorder diagnoses have been investigated in flying phobia. The results of the literature review are presented and related to existing cognitive behavioural theory and research. The results indicate that little research has been conducted into a number of areas considered important in the wider cognitive behavioural literature on anxiety disorders: namely attention, mental imagery, memory, worry and safety-seeking behaviours. The review proposes a hypothetical model, derived from cognitive behavioural theory, for the processes which may be involved in maintaining flying phobia, and considers a number of areas for future research.